A geografia nos anos finais do ensino fundamental na promoção da educação ambiental - Medeiros, Adynamor Lucena de (2017)
The present study aims to analyze the contribution that geography teaching has on promoting environmental education. To this end, we investigate the knowledge and practices of geography teachers of the final years of Elementary School, in Caíco, Rio Grande do Norte. We are motivated by the conviction that geography teaching needs to keep abreast with the theoretical and methodological advances in Brazilian education, faced with the challenge of building knowledge that favors the students‟ education, so that significant improvements in the teaching/learning process are fomented. The necessary areas of knowledge were identified, based on this perspective of revealing new ways for achieving a more critical and reflexive approach to geography teaching, aiming to promote environmental education. In order to that, the study was based on theoretical references about the geography teaching, such as Cavalcanti (2013), Callai (2003), Pontuschka et al., (2009), PCNs de Geografia (BRASIL, 2001), among others that emphasize the environmental education, such as Carvalho (2006), Reigota (2010), Sato; Carvalho (2005), Gutiérrez; Prado (2002), Gadotti (2000). Of these, we highlight the following: the quotidian context; an interdisciplinary approach; and local/global participation and relations. In the context of the study carried out, we propose that the new model for the organization of the curriculum should include a dimension that incorporates provocative themes for teaching geography, to discuss, in depth, ethics and solidarity, performing more sensitive and creative acts in our relation to the environment. This research is considered a case study and the methodological approach to this research is characterized as qualitative in nature, carried out in semi-structured interviews with 20 geography teachers, in schools that include the final years of Elementary school, in the State and City public schools, specifically, in the city of Caicó-RN. The data analyzed reveals that a significant number of teachers recognize the need to incorporate theories and methods of geography teaching to promote environmental education, but we verified that the majority of the teachers do not, as exemplified in the lack of an interdisciplinary practice, as well as, in their utterances which are very tenuous about the students‟ participation in suggesting themes about the environment, which still maintain a strong link with the content presented in the textbooks, with regard to quotidian issues and local/global relations, establishing a type of teaching that lacks significance for and engagement with the students.